Global Early Childhood Caries: A Review of Literature - Shrestha, Ashish; Hoang, Ha; Gardner, Suzanne; Pradhan, Archana; Crocombe, Leonard (Nepal Medical College Journal, 2021)
Early Childhood Caries (ECC) is a major public health concern in the world. There is a high prevalence of ECC in developing countries. The review aimed to synthesise the published literature on the global prevalence of ECC and its associated factors. Researches conducted in Asian, European, American and African countries were included. The review included observational cross-sectional, case-control, cohort studies, and clinical trials. The ECC varies across countries and the continents. Several studies showed inequitable distribution of ECC within regions of a country. The result of this review provides global prevalence of ECC and associated risk factors. Despite the variation of prevalence of ECC, it remains a universal burden. Studies have demonstrated that even in developed countries, ECC represents a significant burden in preschool children. The S. mutans and , oral hygiene habits, breastfeeding and bottle feeding along with factors such as parental education are major risk factors for ECC. There have been limited studies conducted on ECC in Nepal.